2021
DOI: 10.1021/acs.iecr.1c01676
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-Layered Dielectric Film with Intrinsically Excellent Adhesion, Low Dielectric Constant, and Ultralow Dielectric Loss for a High-Frequency Flexible Printed Circuit

Abstract: With the high-frequency development of highspeed communication electronic devices, excellently adhesive materials with low dielectric constant and ultralow dielectric loss have been highlighted. However, intrinsically strong adhesive materials (e.g., epoxy) with numerous polar functional groups disappointingly deteriorate their high-frequency dielectric properties. Herein, a double cross-linked network of maleic-anhydride polybutadiene−amino-terminated polyimide oligomers (MAPB-PIO) is synthesized, and then a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Polymers with excellent dielectric properties have drawn great attention in the field of integrated circuits (ICs), especially for ultra-large-scale integration (ULSI) circuits and high-speed IC packing, as well as for flexible printed circuit boards (FPCBs) at high frequency. [1][2][3][4][5] With the rapid development of ULSI circuits, advanced chips generally integrate billions of transistors. The average size of metal interconnects has shrunk to the order of 10 nm; however, this is accompanied with increased wire resistance and RC signal delay.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers with excellent dielectric properties have drawn great attention in the field of integrated circuits (ICs), especially for ultra-large-scale integration (ULSI) circuits and high-speed IC packing, as well as for flexible printed circuit boards (FPCBs) at high frequency. [1][2][3][4][5] With the rapid development of ULSI circuits, advanced chips generally integrate billions of transistors. The average size of metal interconnects has shrunk to the order of 10 nm; however, this is accompanied with increased wire resistance and RC signal delay.…”
Section: Introductionmentioning
confidence: 99%
“…Based on ternary composite materials (PB/styrene/butadiene/styrene triblock copolymer (SBS)/ethylene/propylene/dicyclopentadiene (EPDM)), Bo and Wu et al found that appropriate crosslinking agents can more effectively enhance the degree of the crosslinking reaction in the material, and the modification of SiO 2 microspheres can improve the interfacial compatibility of different phases [ 15 , 16 , 17 , 18 ]. Xuan and Zhang et al designed a sandwich-structure composite material [ 19 , 20 ], with an intermediate layer of polytetrafluoroethylene (PTFE) and outer layers consisting of PB films or malefic–anhydride polybutadiene–amino-terminated polyamide oligomers films, achieving an ultra-low D f (0.0012). All these developed copper-clad laminate materials with excellent performance have made important contributions to the field of high-frequency substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-large-scale integrated circuits (ICs) with ultrahigh integration, lower power consumption, and higher performance raise more stringent requirements for high-frequency dielectric polymeric materials. Nevertheless, along with the high integration and miniaturization of ICs, mutual interference easily occurs between nearby interconnects, resulting in resistance-capacitance delay and an increase in crosstalk (Zhao and Liu, 2010;Zhang et al, 2021). Therefore, novel polymer materials with controlled dielectric constant and low loss have attracted more and more attention all over the world.…”
Section: Introductionmentioning
confidence: 99%